Pengaruh Struktur Modal, Ukuran Perusahaan, dan Profitabilitas terhadap Nilai Perusahan Perbankan yang Terdaftar di Bursa Efek Indonesia - Keys, Stevani Delpyana Maryani; Edastami, Mayangsari (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to see the impact of Capital Structure, Company Size, and Profitability on the Firm Value of Banking Companies listed on the Indonesia Stock Exchange for the 2019-2023 peiriiod. Quantiitatiivei reiseiarch wiith purposiivei sampliing meithod iis useid as a sampliing teichniiquei. 125 bankiing seictor company data liisteid on thei IiDX for thei 2019-2023 peiriiod weirei studiieid usiing thei Statiistiical Packagei for Sociial Sciieincei (SPSS) reiseiarch tool. Thei analysiis useid iis multiiplei liineiar analysiis iin analyziing thei data. Thei reisults of thiis reiseiarch iindiicatei that Capiital Structurei, Company Siizei, and Profiitabiiliity siimultaneiously havei a posiitiivei eiffeict on Fiirm Valuei. Capiital structurei partiially has a posiitiivei iinsiigniifiicant eiffeict on fiirm valuei. Company siizei partiially has a siigniifiicant neigatiivei eiffeict on fiirm valuei. Thein Profiitabiiliity seiparateily has a siigniifiicant posiitiivei eiffeict on fiirm valuei. Thei liimiitatiion of thiis study iis that reiseiarcheirs only focus on bankiing sub-seictor companiieis. Iit iis hopeid that furtheir reiseiarcheirs can conduct reiseiarch iin otheir seictors such as manufacture and insurance sector financial services. Thiis study iis eixpeicteid to add iinsiight to reiadeirs, company manageimeint, and iinveistors as a steip to makei deiciisiions iin maiintaining company performance, especially those related to the firm value of an entity.